2023
DOI: 10.3390/nu15133003
|View full text |Cite
|
Sign up to set email alerts
|

Athletes with Eating Disorders: Analysis of Their Clinical Characteristics, Psychopathology and Response to Treatment

Abstract: Eating disorders (ED) have frequently been described among athletes. However, their specific features and therapy responses are lacking in the literature. The aims of this article were to compare clinical, psychopathological and personality traits between ED patients who were professional athletes (ED-A) with those who were not (ED-NA) and to explore differences in response to treatment. The sample comprised n = 104 patients with ED (n = 52 ED-A and n = 52 matched ED-NA) diagnosed according to DSM-5 criteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…These individuals can also emphasize appearance and overvalue the belief that lower body weight will improve performance [18]. The study by Ibañez-Caparrós and colleagues included in this issue observed that, when comparing ED patients who were professional athletes with those who were not, the athletes showed less body dissatisfaction and better psychological performance [19]. However, within the athlete group, individual sport activity and aesthetic sports (such as gymnastics, diving, and figure skating) were associated with worse clinical profiles (higher eating-disorder symptom levels and more comorbid psychological problems) and poorer therapy outcomes.…”
Section: Other Risks For Eds (Affecting Any Age Group)mentioning
confidence: 99%
“…These individuals can also emphasize appearance and overvalue the belief that lower body weight will improve performance [18]. The study by Ibañez-Caparrós and colleagues included in this issue observed that, when comparing ED patients who were professional athletes with those who were not, the athletes showed less body dissatisfaction and better psychological performance [19]. However, within the athlete group, individual sport activity and aesthetic sports (such as gymnastics, diving, and figure skating) were associated with worse clinical profiles (higher eating-disorder symptom levels and more comorbid psychological problems) and poorer therapy outcomes.…”
Section: Other Risks For Eds (Affecting Any Age Group)mentioning
confidence: 99%